Prototyping Virtual Mouse Menggunakan Gestur Tangan Berbasis Machine Learning - Rahmawati, Lailia; Efendi, Iqbhal Rizky; Umami, Izzatul (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The development of technology today is experiencing a very rapid increase both in the form of information, data, and systems used to assist human activities in life. Technological innovation is of course also progressing, especially in the field of Artificial Intelligence. A pointing device is a pointing device that functions as navigation on a laptop or computer using a mouse device. This study aims to develop a pointing device without using hardware such as a mouse. With this technology, the cursor can move according to the command without any touch from the hand with the help of a laptop camera or computer instead of a mouse device. This study uses a hand landmark model in which the fingers will be given a point symbol totaling 21. The way this virtual mouse system works is that the user inputs his finger in front of a laptop or computer camera and performs finger gestures to give orders to the cursor. The commands inputted in this system include right click, left click, double click, cursor free movement, and drag